A values‐based health system - Braithwaite, Jeffrey; Skinner, Clare A; Döéry, Mei Ling (Medical journal of Australia, 2011)
We do not have a health system with collaboratively oriented values. Reforms that former prime minister Kevin Rudd initiated, which are now Prime Minister Julia Gillard's to prosecute, do not support such a health system. Reformers have consistently ignored present and potential values. A plan for reform of the health system must take into account differing stakeholders’ objectives and values and incorporate new values. This requires an agreement by stakeholders to embrace the common good. It will also need strong leadership and a willingness to embrace fundamental change.